The engaged university: providing a platform for research that transforms society. Issue 6 (1st August 2010) - Whitmer, Ali; Ogden, Laura; Lawton, John; Sturner, Pam; Groffman, Peter M; Schneider, Laura; Hart, David; Halpern, Benjamin; Schlesinger, William; Raciti, Steve; Bettez, Neil; Ortega, Sonia; et al.
Abstract : Despite a growing recognition that the solutions to current environmental problems will be developed through collaborations between scientists and stakeholders, substantial challenges stifle such cooperation and slow the transfer of knowledge. Challenges occur at several levels, including individual, disciplinary, and institutional. All of these have implications for scholars working at academic and research institutions. Fortunately, creative ideas and tested models exist that provide opportunities for conversation and serious consideration about how such institutions can facilitate the dialogue between scientists and society.